CAT8, a new zinc cluster-encoding gene necessary for derepression of gluconeogenic enzymes in the yeast Saccharomyces cerevisiae. - Hedges, D (1995)
The expression of gluconeogenic fructose-1,6-bisphosphatase (encoded by the FBP1 gene) depends on the carbon source. Analysis of the FBP1 promoter revealed two upstream activating elements, UAS1FBP1 and UAS2FBP1, which confer carbon source-dependent regulation on a heterologous reporter gene. On glucose media neither element was activated, whereas after transfer to ethanol a 100-fold derepression was observed. This gene activation depended on the previously identified derepression genes CAT1 (SNF1) (encoding a protein kinase) and CAT3 (SNF4) (probably encoding a subunit of Cat1p [Snf1p]). Screening for mutations specifically involved in UAS1FBP1 derepression revealed the new recessive derepression mutation cat8. The cat8 mutants also failed to derepress UAS2FBP1, and these mutants were unable to grow on nonfermentable carbon sources. The CAT8 gene encodes a zinc cluster protein related to Saccharomyces cerevisiae Gal4p. Deletion of CAT8 caused a defect in glucose derepression which affected all key gluconeogenic enzymes. Derepression of glucose-repressible invertase and maltase was still normally regulated. A CAT8-lacZ promoter fusion revealed that the CAT8 gene itself is repressed by Cat4p (Mig1p). These results suggest that gluconeogenic genes are derepressed upon binding of Cat8p, whose synthesis depends on the release of Cat4p (Mig1p) from the CAT8 promoter. However, gluconeogenic promoters are still glucose repressed in cat4 mutants, which indicates that in addition to its transcription, the Cat8p protein needs further activation. The observation that multicopy expression of CAT8 reverses the inability of cat1 and cat3 mutants to grow on ethanol indicates that Cat8p might be the substrate of the Cat1p/Cat3p protein kinase.